PERSEPSI NELAYAN LOKAL TERHADAP KEBERADAAN MIMI DI WILAYAH PESISIR BANYUASIN, SUMATERA SELATAN - Dwigothammy, Rahmadella; Fauziyah; Wildayana, Elisa; Agustriani, Fitri (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2024)
Horseshoe crabs (HSC) are marine arthropods, which are protected in Indonesia. Understanding fishermen's perceptions of HSC's existence was very important for the decision-making of conservation planning and management. This research aimed to analyze local fishermen's perceptions toward HSC's existence and the factors influencing their perceptions. Questionnaire-based interviews were conducted with 92 fishermen from the Banyuasin coast, from August to September 2023. Data were analyzed using descriptive statistics and multinomial logistic regression. The results revealed that most fishermen knew HSC and could distinguish their species. The survey of fishing practices showed that the vast majority of respondents operate one-day fishing with only few hours at sea (53.3%), conducting day time operation (69.6%), using 5-10 GT vessels (52.2 %), and deploying fishing gear at the sea bottom (85.9%). Based on fishermen's perception scores toward HSC existence through six assessment aspects, the majority of their perceptions were in the moderate category (54%), followed by the low (28.7%) and high (16.2%) categories. In terms of the regression output, the results of the likelihood ratio test indicated that education, setting position of gear, fishing operation time, and village location were explanatory variables that significantly influenced fishermen's perceptions. Keywords: Ecological knowledge, Fishing practices, Multinomial logistic regression Protected species